Application of telemetry and stable isotope analyses to inform the resource ecology and management of a marine fish. Issue 4 (21st February 2022) - Brownscombe, Jacob W.; Shipley, Oliver N.; Griffin, Lucas P.; Morley, Danielle; Acosta, Alejandro; Adams, Aaron J.; Boucek, Ross; Danylchuk, Andy J.; Cooke, Steven J.; Power, Michael
Abstract: Animal movement and resource use are essential considerations for effective environmental management, but they are challenging to quantify in expansive natural ecosystems such as oceans. We used a novel combination of fish tracking with expansive acoustic telemetry networks, stable isotope analysis and integrated modelling techniques to characterize the spatial and trophic ecology of a marine fish species, permit Trachinotus falcatus, and to address specific resource management needs in the Florida Keys. Tracking‐based movement patterns indicated that permit remained primarily within the designated fisheries management unit (92% of individuals), but they moved frequently among distinct habitat types and fisheries. Movement metrics from 109 individuals were integrated into Bayesian isotope mixing models, revealing variable reliance on seagrass‐ versus offshore/pelagic‐based energy channels amongst individuals. Variance was driven mainly by fish habitat use and home range size (km 2 ). A telemetry‐based regional isoscape, informed by individual‐level estimates of resource use (% seagrass reliance; median = 70%, 29%–100% range), illustrated connectivity among habitats and fisheries. Specifically, seagrass flats were highly connected with the Florida reef tract, with frequent movements between these habitat types and a high reliance on seagrass‐based prey. There was a distinction between these fish and those occupying artificial reefs, with the latter showing high use of pelagic/offshore (i.e. planktonic) energy channels. Synthesis and applications . This study used a novel combination of telemetry, stable isotope analysis and integrated modelling techniques to identify two distinct ecotypes of a nearshore fish species, permit, in the Florida Keys. Of the two ecotypes, nearshore Florida Keys permit support multiple valuable fisheries; for these fish management should prioritize conservation of seagrass flats as a key permit food source, as well as fisheries protection measures at spawning sites on the Florida reef tract. This study highlights the capacity for integrated telemetry‐isotope models to provide key insights into animal ecology that has direct implications for applied environmental management. Abstract : This study used a novel combination of telemetry, stable isotope analysis and integrated modelling techniques to identify two distinct ecotypes of a nearshore fish species, permit, in the Florida Keys. Of the two ecotypes, nearshore Florida Keys permit support multiple valuable fisheries; for these fish management should prioritize conservation of seagrass flats as a key permit food source, as well as fisheries protection measures at spawning sites on the Florida reef tract. This study highlights the capacity for integrated telemetry‐isotope models to provide key insights into animal ecology that has direct implications for applied environmental management.